Biaxially oriented polyester film for thick vapor deposition, film for electrode, and battery
Patent Information
- Application Number
- JP2023128981
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-21
AI Technical Summary
【0010】 本発明によれば、蒸着膜との密着性に優れ、均一に蒸着膜を形成でき、蒸着時に発生する熱によるフィルムのシワを抑制することができる、厚蒸着用二軸配向ポリエステルフィルム、およびそれを用いた電池の電極用フィルムを提供することができる。
Smart Images

Figure 2025024749000001 
Figure 2025024749000002 
Figure 2025024749000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a biaxially oriented polyester film for thick deposition, and a battery electrode film using the same. [Background technology]
[0002] In recent years, the promotion of renewable energy has become increasingly important as a measure to simultaneously reduce greenhouse gas emissions and ensure energy security. In particular, it is difficult to ensure stable output from solar and wind power generation because the amount of power generated depends on weather conditions, and lithium-ion secondary batteries are effectively used in renewable energy power generation facilities.
[0003] Recently, lithium-ion secondary batteries have started to be used in automobiles, including electric vehicles (EVs) and plug-in hybrid electric vehicles (PHEVs), and are also widely used in small electronic devices such as mobile phones, laptops, and portable music players. To miniaturize lithium-ion secondary batteries in line with the development of the portable electronic device market, it is necessary to improve their performance and reliability.
[0004] The electrodes used in these lithium-ion secondary batteries have the function of absorbing (storing) and releasing (releasing) lithium in both the positive and negative electrodes, and lithium ions move to the negative electrode during charging and to the positive electrode during discharging. Each electrode must be in contact with an electrolytic solution or a solid electrolyte to transfer lithium ions between the electrodes, and metal foils with a thickness of about 10 to 30 μm have conventionally been used as the substrate for the electrodes (Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-054339 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, in recent years, as the volumetric energy density has improved due to the increased capacity of lithium-ion secondary batteries, it has become necessary to improve the weight energy density by miniaturizing the batteries, and the electrode base material has been made thinner. However, the conventional technology of thinning the film by rolling metal foil has caused problems such as pinholes that cause the coating liquid to leak through, and insufficient strength against the processing tension that causes cuts or wrinkles.
[0007] In view of the above, an object of the present invention is to provide a biaxially oriented polyester film for thick deposition, which is excellent in adhesion to a deposited film, can form a uniform deposited film, and can suppress wrinkles in the film due to heat generated during deposition by making the electrode substrate of a secondary battery a thick deposited film, thereby achieving a thin electrode substrate, and to provide an electrode film for a battery using the same. [Means for solving the problem]
[0008] As a result of extensive investigations aimed at solving the above problems, it was found that the above problems could be solved by using a biaxially oriented film having specific physical properties as a substrate film, which led to the present invention.
[0009] That is, a preferred embodiment of the biaxially oriented polyester film for thick deposition of the present invention and a battery electrode film using the same have the following configuration. 1. A biaxially oriented polyester film for thick deposition that satisfies the following (1) to (3). (1) The thickness of the biaxially oriented polyester film is 0.5 to 2.0 μm. (2) The intrinsic viscosity (IV value) of the biaxially oriented polyester film is 0.65 to 0.75 (3) The crystal grain size (χc) of the biaxially oriented polyester film is 5.0 to 8.0 nm. 2. The biaxially oriented polyester film for thick deposition according to 1., wherein the number of peaks (SPc) on at least one surface of the biaxially oriented polyester film is 100 to 500. 3. The biaxially oriented polyester film for thick deposition according to 1 or 2, wherein the plane orientation coefficient (fn) of the biaxially oriented polyester film is 0.155 to 0.168. 4. The biaxially oriented polyester film for thick deposition according to any one of 1. to 3., wherein the central surface average roughness (SRa) of at least one surface of the biaxially oriented polyester film is 10 to 50 nm. 5. An electrode film for a secondary battery as described in 4. 6. An electrode film for a lithium ion secondary battery as described in 5. 7. A battery having the electrode film for a secondary battery described in 5. Effect of the Invention
[0010] According to the present invention, it is possible to provide a biaxially oriented polyester film for thick deposition that has excellent adhesion to a deposited film, can form a uniform deposited film, and can suppress wrinkling of the film due to heat generated during deposition, and a film for a battery electrode using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below.
[0012] A preferred embodiment of the biaxially oriented polyester film for thick deposition of the present invention is a biaxially oriented polyester film for thick deposition that satisfies the following (1) to (3). (1) Biaxially oriented polyester film with a thickness of 0.5 to 2.0 μm (2) The intrinsic viscosity (IV value) of the biaxially oriented polyester film is 0.65 to 0.75 (3) The crystal grain size (χc) of the biaxially oriented polyester film is 5.0 to 8.0 nm.
[0013] This embodiment provides a biaxially oriented polyester film for thick deposition that has excellent adhesion to a deposited film, can form a uniform deposited film, and can suppress wrinkling of the film due to heat generated during deposition, and a battery electrode film using the same, which can achieve a thinner electrode base material and contribute to improving the weight energy density by miniaturizing the secondary battery.
[0014] The biaxially oriented polyester film of the present invention is produced by stretching an unstretched resin sheet or film in two directions, the longitudinal direction and the transverse direction, and shows a biaxially oriented pattern by wide-angle X-ray diffraction. As a method for stretching in the biaxial directions, either a sequential biaxial stretching method or a simultaneous biaxial stretching method can be used.
[0015] In the present invention, the term "thick deposition" refers to an application in which a metal deposition of 0.5 μm or more is laminated on both sides or one side, and may be deposited multiple times on the same side. A vacuum process is preferably used as a method for forming a metal deposition film. The vacuum process can be formed by vacuum deposition, sputtering, ion plating, plasma vapor phase epitaxy (CVD), etc. However, in terms of productivity, the vacuum deposition method is currently the most excellent. As a heating means for a vacuum deposition device using the vacuum deposition method, an electron beam heating method, a resistance heating method, or an induction heating method is preferred. In addition, the thickness of the metal layer is generally preferably in the range of 0.5 to 5.0 μm, and more preferably in the range of 1.0 to 3.0 μm. If the film thickness exceeds 5.0 μm, the flexibility of the deposited thin film is lost, and cracks, pinholes, etc. may occur in the thin film due to external forces such as bending and pulling in post-processing steps after film formation. On the other hand, if the film thickness is less than 0.5 μm, the conductivity may decrease and the electrode characteristics (surface resistivity) may decrease.
[0016] The biaxially oriented polyester film for thick deposition of the present invention has a thickness of 0.5 to 2.0 μm. By making the thickness 2.0 μm or less, the weight of the electrode can be reduced, which can contribute to improving the energy density of the battery. From the same viewpoint, the film thickness is more preferably 1.0 to 2.0 μm, and even more preferably 1.5 μm or less. The thickness is determined by the method described in the Examples. Furthermore, by making the thickness 2.0 μm or less, even if the temperature of the film rises due to the heat generated during deposition, it is possible to quickly cool it, thereby suppressing the occurrence of wrinkles and forming a uniform deposition film.
[0017] The intrinsic viscosity (IV, unit: dl / g) of the polyester film is 0.65 or more and 0.75 or less. More preferably, it is 0.67 or more and 0.73 or less. By having an IV of 0.65 or more, the molecular chain is sufficiently long, and molecular mobility is suppressed even in the environment in which the polyester film is subjected to the deposition process, improving heat resistance. Furthermore, by having an intrinsic viscosity of 0.75 or less, the viscosity does not become too high, and breakage during film formation is reduced, improving productivity, and thickness unevenness can be reduced. By reducing thickness unevenness, the deposited film can be made uniform when thickly deposited, improving conductivity, and stabilizing electrode performance. Furthermore, when the thickness is thin as in the present application, by having an IV range of 0.65 or more and 0.75 or less, a uniform deposited film can be formed, and wrinkles in the film due to heat generated during deposition can be suppressed, thereby obtaining a biaxially oriented polyester film for thick deposition.
[0018] The method for adjusting the IV is not particularly limited, but includes a method of performing melt polymerization or solid-phase polymerization in a batch or continuous manner at the stage of polyester raw materials, as in the case of commonly used polyesters. The solid-phase polymerization method is more preferable because the polymerization time is relatively short and the carboxyl end group concentration can be reduced with an increase in viscosity, and adjustment is possible by the solid-phase polymerization time and the amount of catalyst added. In addition, when the polyester raw materials are melt-formed into a polyester film, hydrolysis and thermal decomposition due to the moisture remaining in the molten state progress, so it is preferable that the IV of the polyester raw materials before melt extrusion used as the raw materials for the film is higher than the target value of the IV of the polyester resin constituting the film. Therefore, even if the IV of the polyester resin of the raw materials for the film is higher than the target value of the IV of the polyester resin constituting the film, it is preferable that the difference is small, and the IV of the polyester resin of the raw materials for the film is preferably 0.05 to 0.15 higher than the target value of the IV of the polyester resin constituting the film. In addition, the IV of the film and the raw materials are obtained by the method described in the examples.
[0019] The biaxially oriented polyester film for thick deposition of the present invention has an average crystal grain size (χc) of 5.0 to 8.0 nm. More preferably, it is 6.0 to 7.0 nm. When χc is 5.0 nm or more, the crystals are adjacent to each other without gaps, so that the deposition film becomes uniform when deposited, and the adhesion between the film and the deposition film becomes good, so that the electrode performance can be improved. When χc is less than 5.0 nm, gaps are generated between the crystals, so that the adhesion of the deposition is deteriorated, and it is inconvenient to use it as an electrode. From the viewpoint of productivity and film strength, χc is preferably 8.0 nm or less, but when it exceeds 7.0 nm, the crystals interfere with each other, so that the film becomes embrittled and the puncture strength may decrease.
[0020] Although the method of controlling χc is not particularly limited, examples include a method of controlling the crystallization of the polyester resin by the stretching ratio and heat setting conditions. For example, if the heat setting temperature after stretching is increased or the heat setting time is extended, the crystallization of the polyester resin can be promoted, so that χc tends to increase. On the other hand, if the heat setting temperature is too high or the heat setting temperature is too long, the once crystallized material melts, so that χc tends to decrease. A film having a desired χc value can be obtained by appropriately adjusting the heat setting temperature and time according to the polyester resin constituting the polyester film. The desired χc value can also be obtained by increasing the stretching ratio. χc is determined by the method described in the examples.
[0021] The polyester constituting the biaxially oriented polyester film for thick deposition of the present invention is a general term for polymers in which ester bonds are the main bonding chains of the main chain, but from the standpoints of heat resistance, film formability, etc., those in which ethylene terephthalate and / or ethylene naphthalate units are the main constituent components are preferred.
[0022] The polyester of the present invention may contain other copolymerization components within the range that does not impair the properties, and examples of the dicarboxylic acid components that can be used include aromatic dicarboxylic acids such as diphenyldicarboxylic acid, diphenylsulfonedicarboxylic acid, diphenoxyethanedicarboxylic acid, 5-sodium sulfoisophthalic acid, phthalic acid, and isophthalic acid, aliphatic dicarboxylic acids such as oxalic acid, succinic acid, eicosanoic acid, adipic acid, sebacic acid, dimer acid, dodecanedioic acid, maleic acid, and fumaric acid, alicyclic dicarboxylic acids such as cyclohexynedicarboxylic acid, oxycarboxylic acids such as p-oxybenzoic acid, and polyfunctional acids such as trimellitic acid and pyromellitic acid. On the other hand, examples of the glycol components that can be used include aliphatic glycols such as propanediol, butanediol, pentanediol, hexanediol, neopentyl glycol, and triethylene glycol, alicyclic glycols such as cyclohexanedimethanol, aromatic glycols such as bisphenol A and bisphenol S, diethylene glycol, and polyalkylene glycol. Furthermore, polyethers such as polyethylene glycol and polytetramethylene glycol may be copolymerized.
[0023] These dicarboxylic acid components and glycol components may be used in combination of two or more kinds, or two or more kinds of polyesters may be blended for use.Furthermore, two or more layers may be co-extruded to be used as a laminate film.
[0024] The polyester resin constituting the biaxially oriented polyester film for thick deposition of the present invention is preferably one having ethylene terephthalate and / or ethylene naphthalate units as the main constituent component from the viewpoints of heat resistance and film formability, and more preferably one having ethylene terephthalate units as the main constituent component. Having ethylene terephthalate and / or ethylene naphthalate units as the main constituent component means that the polyester resin contains 70 mol% or more of an ethylene glycol component in 100 mol% of the diol component and contains 70 mol% or more of a terephthalic acid and / or a naphthalenedicarboxylic acid component in 100 mol% of the dicarboxylic acid component.
[0025] Furthermore, the polyester resin constituting the biaxially oriented polyester film may contain polyethylene naphthalate. In this case, when the total mass of the film is taken as 100 mass%, it is preferable from the viewpoint of heat resistance that the content is 0.5 mass% or more and 20 mass% or less. More preferably, it is 1.0 mass% or more and 10 mass% or less. Even more preferably, it is 3 mass% or more and 5 mass% or less. If the content of polyethylene naphthalate is less than 0.5 mass%, the effect of improving heat resistance may not be effective. Also, if the content of polyethylene naphthalate is more than 20 mass%, the compatibility of polyethylene terephthalate and polyethylene naphthalate is poor, making it difficult to form a crystal structure, and the orientation, heat resistance, and moist heat resistance may be reduced due to the increase in the amorphous structure.
[0026] The biaxially oriented polyester film is preferably a biaxially oriented polyethylene terephthalate film / or a biaxially oriented polyethylene naphthalate film, and more preferably the biaxially oriented polyester film is a biaxially oriented polyethylene terephthalate film.
[0027] The biaxially oriented polyester film preferably has a melting point of 250° C. or more and 280° C. or less. By setting the melting point to 250° C. or more, durability against heat load during processing is improved.
[0028] The biaxially oriented polyester film preferably has a carboxyl end group amount of 25 to 55 equivalents / ton, more preferably 35 to 50 equivalents / ton. By making the carboxyl end group amount 25 equivalents / ton or more, the adhesion between the polyester film and the vapor-deposited film during vapor deposition is improved. In addition, by making the carboxyl end group amount 55 equivalents / ton or less, problems such as coloration of the polyester film and deterioration of the film formability of the polyester film can be suppressed.
[0029] In the biaxially oriented polyester film for thick deposition of the present invention, the amount of diethylene glycol in the film is preferably 1.5% by mass or less. More preferably, it is 1.2% by mass or less, and even more preferably, it is 1.0% by mass or less. By setting the amount of diethylene glycol in the film within the above-mentioned range, the deposited film becomes uniform when deposited, and the electrode performance can be stabilized. Furthermore, the heat resistance of the film is reduced due to the heat history of the polyester film in the deposition process, and the film stretches against an external force in the subsequent processing process, causing wrinkles, or the running property of the film becomes unstable, and the processability is deteriorated. In addition, various additives, such as heat stabilizers, oxidation stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic fine particles, fillers, nucleating agents, etc., may be blended into the polyester resin within a range that does not impair the effects of the present invention.
[0030] Representative examples of particles that can be contained in the biaxially oriented polyester film for thick deposition of the present invention include inorganic particles such as particles, aggregates, silicon dioxide particles, calcium carbonate particles, alumina particles, titanium oxide particles, barium sulfate particles, aluminum silicate particles, calcium phosphate particles, mica, kaolin, and clay generated by various nucleating agents during polymerization, and organic particles such as crosslinked polystyrene particles, acrylic particles, imide particles, and silicone particles, or mixtures thereof. Among these, inorganic particles such as silicon dioxide particles, calcium carbonate particles, alumina particles, and aluminum silicate particles, or mixtures of these inorganic particles and particles generated by various nucleating agents during polymerization, are preferred. The diameter of the various particles used is not particularly limited, but representative examples include particles having an average particle diameter of 0.05 to 8.0 μm, preferably 0.1 to 4.0 μm, as measured by a sedimentation method or a light scattering method. The content of such particles is preferably 0.01 to 0.20% by mass, more preferably 0.02 to 0.15% by mass, based on the entire film.
[0031] The biaxially oriented polyester film for thick deposition of the present invention preferably has a three-dimensional roughness of 100 to 500 projections per unit area (SPc) on both sides. SPc is the number of projections exceeding 2.5 nm within 0.2 mm of the film surface, with the height of the center plane of the roughness curved surface as the zero baseline. 2 The number of particles is counted per unit area. If the number of particles is less than 100, the adhesion of the deposited film will be poor, and it may not be possible to obtain sufficient adhesion as an electrode. Furthermore, the film will become difficult to wind up, resulting in poor productivity. The method for measuring SPc will be described later. If the number of particles is more than 500, the smoothness of the film will be lost, and deposition may not be uniform.
[0032] The biaxially oriented polyester film for thick deposition of the present invention preferably has a plane orientation coefficient (fn) of 0.155 to 0.168. More preferably, it is 0.158 to 0.165. Within the above range, the film has good orientation, is less likely to lose strength or stretch due to external force, and has good suitability for deposition processing. In addition, the adhesion to the deposition film is good, and peeling and falling off of the deposition film can be suppressed in the processing step after deposition. If it is less than 0.155, problems such as wrinkles are likely to occur during processing, and if it exceeds 0.168, the deposition film is likely to peel off due to cleavage of the film, etc., and problems may easily occur during processing. The plane orientation coefficient (fn) of the film is determined by the method described in the examples.
[0033] The biaxially oriented polyester film for thick deposition of the present invention preferably has a center surface average roughness (SRa) of 10 to 50 nm on at least one surface. More preferably, it is 20 to 40 nm. The center surface average roughness SRa is a parameter of three-dimensional surface roughness obtained by a measurement method described later. By setting the SRa within the above-mentioned range, the adhesion surface area with the deposition film during deposition processing is increased, and sufficient adhesion as an electrode can be obtained. Furthermore, the slipperiness is also good, making it easy to wind up in the processing step and suppressing the occurrence of blocking. On the other hand, if the SRa is less than 10 nm, the adhesion surface area with the deposition film is reduced, and sufficient adhesion as an electrode may not be obtained. Furthermore, the winding property of the film may deteriorate, and productivity may decrease. Also, if it exceeds 50 nm, protrusions may induce uneven deposition during deposition processing, thereby reducing electrode performance.
[0034] The biaxially oriented polyester film for thick deposition of the present invention preferably has a melting subpeak (Tmeta) of the film of 225°C or more. More preferably, it is 228°C or more, and even more preferably, it is 230°C or more. When Tmeta is 225°C or more, the thermal crystallization of the polyester film proceeds sufficiently, and the average crystal grain size (χc) described above is easily set in the above-mentioned range. Therefore, the deposited film becomes uniform when deposited, and the electrode performance can be improved. Furthermore, the thermal dimensional stability at high temperatures can be improved, and the film is less likely to stretch due to the heat of the deposited metal during deposition processing, and the uniformity of the deposited film can be maintained.
[0035] The melting sub-peak of the film is obtained by the following measurement. The film is measured with a differential scanning calorimeter (DSC Q100 manufactured by TA Instruments) at a heating rate of 20°C / min to obtain the melting peak temperature (melting point), and the minute endothermic peak temperature generated by the transformation of the pseudocrystal during this measurement is defined as Tmeta. Note that Tmeta appears as the history of the heat treatment temperature for the polyester film.
[0036] The biaxially oriented polyester film for thick deposition used in the present invention may have a single layer structure, or a laminate structure consisting of resin compositions A, B, and C with different compositions, such as a two-layer structure of A / B, a three-layer structure of A / B / A or A / B / C, or a laminate structure with more than three layers. The lamination thickness ratio in this case may also be set arbitrarily. These laminate structures can be produced as laminate films by coextrusion.
[0037] A preferred embodiment of the method for producing a biaxially oriented polyester film for thick deposition according to the present invention will be specifically described below, although the present invention is not limited to the following method.
[0038] The polyester resin used in the biaxially oriented polyester film for thick deposition of the present invention preferably has a melting point of 250° C. or higher in terms of heat resistance and film formability. Commercially available polyester resins can be used as they are, but they may also be produced through a polycondensation reaction as described below and used.
[0039] 0.09 parts by mass of magnesium acetate and 0.03 parts by mass of antimony trioxide are added to a mixture of 100 parts by mass of dimethyl terephthalate and 70 parts by mass of ethylene glycol, and the mixture is gradually heated, and finally, at 220°C, an ester exchange reaction is carried out while distilling off methanol, to synthesize a precursor of polyethylene terephthalate. Next, 0.02 parts by mass of an 85% aqueous solution of phosphoric acid (molar concentration 14.6 mol / L) is added to the precursor, and the mixture is transferred to a polycondensation reaction vessel. The reaction system is gradually depressurized while heating and increasing the temperature in the polycondensation reaction vessel, and a polycondensation reaction is carried out at 290°C under a reduced pressure of 1 hPa, to obtain a polyester resin having a desired molecular weight. When particles are added, it is preferable to add a slurry in which particles are dispersed in ethylene glycol to the polycondensation reaction vessel so as to achieve a predetermined particle concentration, and then carry out the polycondensation reaction.
[0040] In order to improve adhesion to the vapor-deposited film, the amount of diethylene glycol (DEG) in the polyester resin can be reduced by, but not limited to, shortening the polymerization time, limiting the amount of antimony compounds, germanium compounds, titanium compounds, etc. used as polymerization catalysts, combining liquid-phase polymerization with solid-phase polymerization, or adding an alkali component. For example, when potassium hydroxide is added to adjust the amount of DEG, a polyester resin with a DEG amount of 0.01 to 1.5% by mass can be obtained by adding 0.01 to 0.10 parts by mass per 100 parts by mass of dimethyl terephthalate.
[0041] Next, a preferred method for producing the battery electrode film of the present invention using a polyester resin will be specifically described. First, the polyester resin to be used is heated under reduced pressure or in a nitrogen atmosphere, and dried, for example, at 150°C for 5 hours, preferably to reduce the moisture content in the resin to 50 ppm or less.
[0042] Then, the resin is fed to an extruder to perform melt extrusion. When a vent-type twin-screw extruder is used, the drying step may be omitted. When a plurality of polyester resins are mixed and used, they may be mixed in a drying step to a predetermined mixing ratio, or the mixing ratio may be measured when feeding the resin to the extruder. The resin thus melt-extruded is filtered to remove foreign matter while in the molten state, the extrusion amount is measured by a gear pump, and the resin is extruded as a molten sheet from a T-die having a slit-shaped discharge port, and is solidified by adhering to a cooling roll to obtain a cast film (unoriented film (unstretched film)). In order to improve the adhesion between the molten sheet and the cooling roll, it is usually preferable to adopt an electrostatic application adhesion method and / or a liquid surface application adhesion method. The cast film is biaxially stretched. First, the film is heated by a group of rolls heated to a temperature higher than the glass transition temperature of the polyester resin, for example, 90°C to 135°C, more preferably 100°C to 130°C, by heating the film with two or more infrared heaters for full width heating and end heating, and stretched 4.0 to 5.5 times in the film longitudinal direction (MD) to obtain a uniaxially oriented film (uniaxially stretched film). Next, the film is stretched 3.5 to 5.0 times in the film transverse direction (TD), preferably at a temperature higher than 100°C and lower than 130°C.
[0043] The film thus obtained is preferably subsequently heat-set in-line and / or off-line. Furthermore, if necessary, the film may be stretched again in MD and / or TD before or after heat-setting. The heat-setting temperature is preferably 220 to 245°C, more preferably 225 to 245°C in order to further improve the gas barrier property, and particularly preferably 230 to 245°C. The heat treatment time is usually 1 second to 1 minute. In addition, in this heat-setting step, the heat shrinkage properties can be adjusted by performing a relaxation treatment in the longitudinal direction and / or the transverse direction.
[0044] After the heat setting, a polyester film with complete crystal orientation can be obtained by passing through a cooling zone at 100 to 200° C. For example, after heat setting, the film can be rapidly or slowly cooled, or an intermediate cooling zone can be provided to adjust the heat shrinkage stress.
[0045] The film may be coated as necessary. By providing a coating layer on the film, the adhesion to the deposition layer and the conductive ink layer in particular can be improved. The coating liquid is dissolved in water, emulsified or suspended in consideration of explosion-proofing and environmental pollution. The coating layer may be applied to a biaxially stretched film after completion of crystal orientation or to a film before completion of crystal orientation and then stretched. The latter method is particularly preferred in order to more significantly exhibit the effects of the present invention. The method of application is not particularly limited, but it is preferable to apply the coating using a roll coater, gravure coater, reverse coater, kiss coater, bar coater, etc. In addition, the surface to be coated may be subjected to corona discharge treatment in air or other various atmospheres before coating, as necessary.
[0046] The coating layer may contain antifoaming agents, coating crosslinking agents, thickeners, organic lubricants, inorganic particles, antioxidants, ultraviolet absorbers, foaming agents, dyes, pigments, and the like, as required.
[0047] The biaxially oriented polyester film for thick deposition of the present invention is preferably used as an electrode film for a secondary battery because the base film is thin and has excellent heat resistance. By doing so, the resistance characteristics of the battery sheet are improved among the electrode performance of the secondary battery, and in particular, the electrical conductivity is improved and the electrode performance is stabilized, so that it is more preferably used as an electrode film for a lithium ion secondary battery.
[0048] A preferred embodiment of the battery of the present invention is a battery having the biaxially oriented polyester film for thick deposition described above. This embodiment allows the film to be thin but have few pinholes and to withstand processing tension, and improves the resistance characteristics of the electrode sheet, leading to improved battery performance such as high output and long life. EXAMPLES
[0049] The film of the present invention will be described in more detail below using examples, but the film of the present invention is not limited to the embodiments shown below. [Methods of measuring characteristics and evaluating effects] (1) Thickness Ten stacked test pieces were measured using a micrometer in accordance with JIS C2151 (2019). The thickness measurement was divided by 10 to obtain the thickness at each measurement point, and the average value was obtained.
[0050] (2) Intrinsic viscosity (IV) The polyester resin or polyester film was dissolved in 100 mL of orthochlorophenol (solution concentration C = 1.2 g / mL), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. The viscosity of the solvent was also measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] was calculated according to the following formula (1), and the obtained value was taken as the intrinsic viscosity (IV). ηsp / C=[η]+K[η]2·C...Equation (1) (Here, ηsp = (solution viscosity / solvent viscosity)-1, and K is the Huggins constant (assumed to be 0.343).)
[0051] In addition, when the solution in which the polyester resin or polyester film was dissolved contained insoluble matter such as inorganic particles, the solution was filtered and the mass was measured, and a correction was performed in which the mass of the filtered matter was subtracted from the mass of the measured sample to obtain the measured sample mass.
[0052] (3) Average grain size (χc) The diffraction intensity of the sample was measured using a PHILIPS Compact X-ray Diffractrometer System PW1840 with Cu Kα radiation (wavelength 0.1542 nm) as a light source under the following conditions. Scanning range: 18~32° Scanning speed: 0.05° / sec Accelerating voltage: 35 kV Bulb current 15mA The average crystal grain size (χc) is the half-width of the maximum peak β (rad), χc=kλ / βcosθ Calculation was performed using k: constant (0.9) of the Scherrer equation for X-ray diffraction, λ: wavelength of X-rays (nm), β: half-width of the maximum peak (rad), and θ: diffraction angle of the maximum peak.
[0053] (4) The average roughness SRa of the central surface of the film and the number of three-dimensional surface protrusions SPc Measurements were carried out by the stylus method under the following conditions using a three-dimensional surface roughness meter (ET4000AK, manufactured by Kosaka Laboratory). The central surface average roughness SRa is the difference between the height of the rough curved surface of the target surface and the height of the central surface of the rough curved surface, and is expressed as the average of the absolute values. The three-dimensional surface protrusion count SPc is the number of protrusions exceeding 2.5 nm, measured within 0.2 mm of the film surface, with the height of the central surface of the rough curved surface as the zero baseline. 2 It was counted by hit. Needle diameter 2μmR Needle pressure 10mg Measurement length 500μm Vertical magnification: 20,000 times CUT OFF 250μm Measurement speed 100μm / s Measurement interval: 5μm Record number: 80 Hysteresis width ±6.25nm Reference area 0.1mm 2 .
[0054] (5) Plane orientation factor (fn) The refractive indexes in the longitudinal direction (nMD), width direction (nTD), and thickness direction (nZD) were measured using an Abbe refractometer with sodium D line (wavelength 589 nm) as a light source and diiodomethane as an intermediate liquid. The plane orientation coefficient fn was calculated using the following formula. fn={(nMD+nTD) / 2}-nZD.
[0055] (6) Adhesion of evaporated film The film was evaporated in a continuous vacuum deposition machine for 10 -4The pressure was reduced to below Torr, 99.99% pure aluminum metal was loaded into an alumina crucible from the bottom of the cooling drum, the aluminum metal was heated and evaporated, and deposited on the film to form an aluminum film with a thickness of 1 μm. This process was repeated three times. The opposite side was also vapor-deposited three times in the same way, yielding a vapor-deposited sample with a 3 μm metal layer on both sides.
[0056] Next, an adhesive prepared by mixing Toyo Morton's "Adcoat" (registered trademark) 503 (AD503), hardener CAT-10, and ethyl acetate in a ratio of 100:5:100 (mass ratio) was applied to the deposition surface of the sample using a #12 Mayer bar. After application, the adhesive was dried for 30 seconds in a hot air oven at 70°C, and then laminated to the corona-treated surface of a 60 μm-thick unstretched polypropylene film, and aged for 72 hours at 40°C using a hot air oven. The laminated sample was cut to a width of 15 mm, and the peel force between the polypropylene film and polyester film was measured at a peel angle of 90° using Orientec's "TENSILON" (registered trademark) UCT-100 under an atmosphere of room temperature of 23°C and relative humidity of 65%. A:400g / 15mm width or more B: 200g / 15mm width or more, 400g / 15mm width or less C: Less than 200g / 15mm width.
[0057] (7) Uniformity of the deposited film The double-sided deposition sample obtained in (6) was sampled at five locations spaced 50 mm apart. Next, the cross section of the deposition layer of the deposition sample was observed at a magnification of 10,000 times using a Hitachi S-2100A scanning electron microscope, and the thickness of the deposition layer on both sides of each sample was measured. Of the ten measured values, the minimum value was subtracted from the maximum value, and the thickness was evaluated according to the following three levels. A: Less than 0.2 μm B: 0.2μm or more, less than 0.4μm C: 0.4 μm or more.
[0058] (8) Visual inspection of deposition surface The double-sided deposition sample obtained in (6) was cut to a width of 200 mm and a length of 300 mm, and visually observed under a fluorescent lamp to evaluate the state of thermal wrinkles on the deposition surface on a three-level scale. A: No heat wrinkles were observed on the deposition surface. B: Thin heat wrinkles were partially observed on the deposition surface. C: Heat wrinkles were observed over the entire deposition surface.
[0059] Next, the polyester film of the present invention will be specifically described with reference to examples. In the examples, "parts" refers to "parts by mass" unless otherwise noted.
[0060] [Production of polyethylene terephthalate] The polyethylene terephthalate resin was prepared as follows.
[0061] (1) Polyethylene terephthalate resin (PET-1) To a mixture of 100 parts by mass of dimethyl terephthalate and 61 parts by mass of ethylene glycol, 0.04 parts by mass of magnesium acetate and 0.02 parts by mass of antimony trioxide were added, and the temperature was gradually raised, and finally, at 220°C, an ester exchange reaction was carried out while distilling off methanol. Next, 0.020 parts by mass of an 85% aqueous solution of phosphoric acid was added to the ester exchange reaction product, and then the mixture was transferred to a polycondensation reaction vessel. Furthermore, the reaction system was gradually depressurized while heating and raising the temperature, and a polycondensation reaction was carried out at 290°C under a reduced pressure of 1 hPa by a conventional method, to produce a polyethylene terephthalate resin (hereinafter referred to as "PET-1") having a diethylene glycol content of 1.45% by mass, an intrinsic viscosity of 0.65 dl / g, and 95 mol % or more of the acid component was composed of terephthalic acid, and 95 mol % or more of the glycol component was composed of ethylene glycol. The intrinsic viscosity of the polyethylene terephthalate resin PET-1 in the table was adjusted by the polymerization time by the solid-phase polymerization method.
[0062] (2) Particle Master When producing the polyethylene terephthalate (1) above, after the transesterification reaction, an ethylene glycol slurry of aggregated silica particles having a median diameter (average particle diameter) of 2.1 μm as measured using a laser diffraction / scattering particle size distribution analyzer LA-700 (manufactured by Horiba, Ltd.) was added, and then a polycondensation reaction was carried out to obtain a particle master (hereinafter referred to as "PET-2") having a particle concentration of 2.0 mass%.
[0063] Example 1 PET-1 was mixed at a ratio of 90 parts by mass and 10 parts by mass of PET-2 and used. The mixture of PET-1 and PET-2 was vacuum dried, then fed to an extruder, melt-extruded at 280°C, filtered through a 14μm cut stainless powder sintered filter (PSS), extruded into a sheet from a T-shaped die, and cooled and solidified by electrostatic adhesion onto a cooling drum with a surface temperature of 25°C. The unstretched (unoriented) PET film thus obtained was heated to 125°C and stretched 4.5 times in the longitudinal direction to form a uniaxially stretched film. This film was stretched 3.8 times in the width direction while being heated to 110°C (transverse stretching). This film was introduced into hot air at 235°C and heat-treated (heat-set) for 2 seconds without relaxation in both the MD and TD directions, and then relaxed (relaxed) at 150°C in the width direction by 4.0% relative to the film width after TD stretching, and cooled. In this way, a polyester film with a thickness of 0.5μm was finally obtained.
[0064] Aluminum was vapor-deposited at a predetermined vapor deposition rate on the polyester film thus obtained with a thickness of 0.5 μm. The method of vapor-depositing aluminum was as follows: the film was set on the unwinding device of a continuous vacuum vapor-depositing machine, and the film was wound up by running it over a cooled metal drum. At this time, the continuous vacuum vapor-depositing machine was rotated for 10 -4 The pressure was reduced to below Torr, 99.99% pure aluminum metal was loaded into an alumina crucible from the bottom of the cooling drum, and the aluminum metal was heated and evaporated, deposited on the film, and the process of forming an aluminum film with a thickness of 1 μm was repeated three times. The opposite side was also vapor-deposited three times in the same way, forming an aluminum vapor-deposited film with a thickness of 3 μm on both sides, resulting in a vapor-deposited film with a total thickness of 6.5 μm.
[0065] (Examples 2 to 12, Comparative Examples 1 to 8) As shown in the table, polyester films and aluminum vapor deposition films were obtained in the same manner as in Example 1, except that the film-forming conditions (polyethylene terephthalate resin mixing ratio, longitudinal stretching conditions, and heat setting conditions) were changed, and the thickness when extruded into a sheet from the T-shaped die was changed. The results are shown in the table. The raw material resin used in Comparative Example 6 was the raw material resin (IV=0.61) used in Example 1 of JP-A-2011-174009. The raw material resin used in Comparative Example 7 was the raw material resin (IV=0.65) used in Example 1 of JP-A-10-40919. The raw material resin used in Comparative Example 8 was the raw material resin (IV=0.65) used in Example 1 of JP-A-10-40920.
[0066] The deposited films using the polyester films obtained in the Examples as substrates were excellent in adhesion to the deposited film, uniformity of the deposited film, and wrinkles during deposition. On the other hand, the aluminum deposited films using the polyester films obtained in the Comparative Examples 1 to 8 as substrates were inferior.
[0067] [Table 1]
[0068] [Table 2]
[0069] [Table 3] [Industrial Applicability]
[0070] According to the present invention, it is possible to provide a biaxially oriented polyester film for thick deposition, which has excellent adhesion to a deposited film, can form a uniform deposited film, and can suppress wrinkling of the film due to heat generated during deposition. This makes it possible to achieve a thinner electrode substrate and contribute to improving the weight energy density by miniaturizing the secondary battery.
Claims
1. A biaxially oriented polyester film for thick deposition that satisfies the following (1) to (3): (1) The thickness of the biaxially oriented polyester film is 0.5 to 2.0 μm. (2) The intrinsic viscosity (IV value) of the biaxially oriented polyester film is 0.65 to 0.
75. (3) The crystal grain size (χc) of the biaxially oriented polyester film is 5.0 to 8.0 nm.
2. 2. The biaxially oriented polyester film for thick deposition according to claim 1, wherein the number of peaks (SPc) on at least one surface of the biaxially oriented polyester film is 100 to 500.
3. The plane orientation coefficient (fn) of the biaxially oriented polyester film is 0.155 to 0.168 3. The biaxially oriented polyester film for thick deposition according to claim 1 or 2,
4. The center surface average roughness (SRa) of at least one surface of the biaxially oriented polyester film is 10 to 50 nm.
3. The biaxially oriented polyester film for thick deposition according to claim 1 or 2.
5. The electrode film for a secondary battery according to claim 4 .
6. The electrode film for a lithium ion secondary battery according to claim 5 .
7. A battery comprising the electrode film for a secondary battery according to claim 5 .
Citation Information
Patent Citations
Thin-film electrode, and laminated battery
JP2011054339A